Enhanced Influence of Late‐Winter Arctic Oscillation on Early Spring Temperature in North and Northeast Asia - Xin Zhou; Tingting Han; Huijun Wang; Botao Zhou; Shengping He (Earth's Future)
Abstract Numerous studies have highlighted the simultaneous relationship between the Arctic Oscillation (AO) and weather/climate in Asia. However, the stability of the precursor signals in AO for Asian surface air temperature (SAT), which is important for short‐term climate prediction, has received little attention. In this study, a strengthened relationship is identified between the late‐winter AO and the early spring SAT over North and Northeast Asia (NNA) around the 1990s. During 1990–2022, a positive (negative) phase of AO during late winter is generally followed by significant warming (cooling) anomalies in the NNA during early spring, whereas this relationship is insignificant during 1961–1987. Further result shows a good persistence of the late‐winter AO to early spring after the 1990s. Accordingly, the AO exerts a strengthened impact on Mongolian anticyclone and Asian westerly anomalies through modulation of a Rossby wave train that propagates from the Arctic to the NNA in early spring, leading to significant SAT anomalies at NNA. Additionally, the AO‐related temperature anomalies intensified in the stratosphere after the 1990s, linking AO and stratospheric polar vortex (SPV). The intensified (weakened) SPV following positive (negative) AO facilitates warming (cooling) anomalies at NNA via downward‐propagating Eliassen‐Palm fluxes at wave number 1 and circumpolar westerlies in middle and lower troposphere. The seasonal persistence of AO and the strengthened relationship between AO and SPV synergistically enhance the influence of late‐winter AO on early spring SAT in the NNA, which might be attributed to the interdecadal changes in background circulation over the Arctic.